AB0035 Angiopoietins: the missing link in poems syndrome?. (15th June 2017) - Coutant, F; Tatar, Z; Rouzaire, P; Evrard, B; Dosgilbert, A; Tournilhac, O; Guenno, G Le; Lemal, R; Soubrier, M
Abstract : Background: POEMS syndrome (Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal gammopathy and Skin changes) is a rare multiorgan disease related to plasma cell dyscrasia. The pathogenesis of the POEMS syndrome is currently unknown, but microangiopathy involving neoangiogenesis and increased vascular permeability may explain some of the features of the disorder. Although vascular endothelial growth factor (VEGF) is constantly highly abundant in the serum of patients with POEMS syndrome, therapeutic approaches targeting the VEGF have led to conflicting results, suggesting that other mediators sharing functional similarities with the VEGF contribute to the pathogenesis. Angiopoietins are known to be involved in the development, remodeling and stability of blood vessels. It is thus tempting to speculate that altered expression of angiopoietins might contribute to the pathogenesis. Objectives: The aim of this study was to evaluate the circulating levels of three major angiogenic cytokines in patients before and after treatment: VEGF, angiopoietin-1, which plays an essential role in the stabilization and the maturation of blood vessels, and angiopoietin-2 that facilitates angiogenesis in the presence of VEGF. Methods: Circulating levels of VEGF, Angiopoietin-1 and angiopoietin-2 were determined by ELISA in the serum of 3 patients with POEMS syndrome, before and after therapy. All patients had polyneuropathy, organomegaly, a monoclonal gammopathy (2 IgAl, 1 IgGk) and osteosclerotic lesions. Two patients had typical skin lesions, oedema and one patient had a Castleman disease. Results: As expected, the serum of patients before treatment exhibited high levels of VEGF (2901±920 pg/mL). Strikingly, angiopoietin-1 levels were highly abundant before treatment (67286±20395 pg/mL) and successful treatment led to a strong reduction in both VEGF and angiopoietin-1. Angiopoietin-1 levels strongly correlated with levels of VEGF (r=0.83). By contrast, angiopoietin-2 levels did not differ significantly before and after treatment. Conclusions: Thus, angiopoietin-1 seems to be a crucial proangiogenic cytokine overproduced in patients with POEMS syndrome that might explain some of the features of the pathology. The overproduction of VEGF and angiopoietin-1 is likely to promote manifestations encountered in POEMS syndrome such as organomegaly, osteosclerotic lesions or glomeruloid hemangioma. Restoring the balance between angiopoitein-1, angiopoietin-2 and VEGF could constitute a very promising therapeutic strategy in this disease. Disclosure of Interest: None declared